Glycolytic rate (PET) and contrast enhancement (CT) in human cerebral gliomas. - Patronas, N J; Brooks, R A; DeLaPaz, R L; Smith, B H; Kornblith, P L; Di Chiro, G (American Journal of Neuroradiology, 1983)
A comparison of the glycolytic rate as determined by positron emission tomography (PET) with 18F-deoxyglucose (FDG) and cerebral contrast computed tomography (CT) was carried out in 72 cases of cerebral glioma. FDG-PET is more accurate than contrast CT in predicting tumor grade.